Peningkatan Kualitas Laporan Keuangan UMKM Kuliner Tradisional di Yogyakarta (International Forum of Researchers and Lecturers, 2024)
This community service was conducted on Jalan Jembatan Merah I and Jalan Wisata Babarsari. The purpose of this community service is to improve the quality of financial record-keeping, ensuring accuracy and correctness, to provide an accurate overview of the financial condition of UMKM Siomay Indul and Gudeg Jogya Mak Karti. This community service is focused on enhancing the quality of the financial reports of these UMKMs through understanding and implementing proper accounting practices in financial record-keeping. With the provision of training and mentoring, it is expected that the stakeholders of traditional culinary UMKMs can optimize their business potential. The results of the community service indicate that improvements in transaction recording systems and a better understanding of accounting standards can significantly enhance the quality of financial reports, providing the clarity needed for better decision-making in business management.